Thinking about biology - Webster, Stephen, 1957- (Cambridge University Press, 2003)
"Thinking About Biology is intended for biology students who are interested in reflecting on the wider contexts of their studies. The book encourages students to see that biology does not deliver certainties; it discusses how biological ideas become established facts; and it uses history to examine how ideas change and to show that the biological fact that form the basis of a biology course are also likely to change." "Each chapter is based on biological topics, and examines them for their philosophical, social and political implications. Topics covered include the role of natural selection in evolution, the history of ideas about fertilisation and inheritance, vivisection and reductionism. Genetically modified foods, xenotransplantation, eugenics and genetic testing are some of the controversial subjects discussed." "Thinking About Biology should be essential reading for all college students already taking a course in the biological sciences, and for those contemplating such a course in the future."--Jacket